Religion and Education among Latinos in New York City - Pantoja, Segundo (Religion in the Americas, 2005)
This volume explores the role of religion in the educational achievement of Hispanics. In particular, it assesses the influence of religion on parental involvement in children's educational experiences. The book compares Catholic and Protestant parents' opinions and practices against the backdrop of socio-economic factors, such as levels of income and schooling. In its examination of the relationships between family, church and school, the study explores how religion and other cultural traits such as family structure, language, and ethnic identity, interact and yield particular educational outcomes. The study shows that religion can make a positive difference in the education of Latinos. Religion is a resource that parents can tap into for the benefit of their children. Teachers, school administrators, policy makers and religious leaders will find this study useful as they strive to understand and change Latinos' educational status.